Effects of Pediococcus pentosaceus LI05 on immunity and metabolism in germ-free rats. Issue 11 (7th May 2021) - Jiang, Shiman; Xia, Jiafeng; Lv, Longxian; Wang, Qiangqiang; Li, Yating; Xu, Qiaomai; Bian, Xiaoyuan; Ye, Jianzhong; Yang, Liya; Jiang, Huiyong; Yan, Ren; Wang, Kaicen; et al.
Abstract : Many Pediococcus spp. have health-promoting benefits, and Pediococcus pentosaceus LI05 is one such species that was proved to be beneficial in previous studies. Abstract : Many Pediococcus spp. have health-promoting benefits, and Pediococcus pentosaceus LI05 is one such species that was proved to be beneficial in previous studies. Our research aimed to determine the immune and metabolic effects of P. pentosaceus LI05 on germ-free rats. Germ-free rats were gavaged with P. pentosaceus LI05 suspensions (1 × 10 9 CFU) for 2 weeks, and 3 weeks later, blood, spleen, intestine and liver samples were gathered for metabolome, intestine morphology, immunity, and transcriptomics analyses. Oral gavage of P. pentosaceus LI05 reduced the bodyweight of rats, which manifested as increased fecal carbohydrate concentrations, decreased intestinal fat intake and the hepatic fat synthesis gene expression, and accelerated fat-to-glycogen conversion. In addition, P. pentosaceus LI05 exhibited an anti-inflammatory ability, reducing serum proinflammatory cytokine levels and increasing intestinal subepidermal CD4 + cell levels. Furthermore, administration of P. pentosaceus LI05 increased the antimicrobial ability and enhanced the liver detoxification function. These results indicate that as a probiotic, P. pentosaceus LI05 ameliorates the hampered immune response of GF animals and improves the metabolism of fat and toxic substances.